Effects of Gabapentin Enacarbil on Postoperative Pain After Hip and Knee Arthroplasty: A Placebo-controlled Randomized Trial. Issue 4 (7th April 2022) - Ayad, Sabry S.; Makarova, Natalya; Niazi, Azfar K.; Khoshknabi, Dilara S.; Stang, Taylor; Raza, Syed; Kim, Daniel D.
Abstract : Objectives: Total joint arthroplasties are among the most common elective procedures performed in the United States, and they are associated with postoperative pain. Gabapentin enacarbil is a prodrug with an extended-release formulation that has been proposed for multimodal postoperative analgesia, but the drug's efficacy for major arthroplasties remains unclear. Materials and Methods: We enrolled 60 adult patients scheduled for primary knee or hip arthroplasty expected to remain hospitalized for at least 3 days. Eligible patients were randomly assigned to placebo or gabapentin enacarbil 600 mg twice daily starting the day before surgery continuing for 3 days thereafter. The primary outcome was analyzed using a joint hypothesis framework of pain (0 to 10 verbal response scores) and cumulative opioid consumption (mg of morphine equivalent) within the first 72 hours. Secondary outcomes were nausea and vomiting, pain persisting 90 days after surgery, duration of hospitalization, and early postoperative health status using quality of recovery score (QoR-15). Results: Twenty-eight patient in gabapentin enacarbil group and 32 in placebo group were analyzed. Since pain scores did not differ significantly (difference of means: −0.2 in pain scores; 95% confidence interval: −1.1, 0.7), nor did opioid consumption, conditions for joint hypothesis testing were not met. Moreover, there were no significant differences between groups for secondary outcomes. Discussion: We did not identify statistically significant or clinically meaningful differences in our primary and secondary outcomes related to perioperative use of gabapentin enacarbil in patients having primary hip or knee arthroplasties.